Influence of summer dung deposition on estimated yellow bristle grass (Setaria pumila) seed production - Gerard, P.J.; Cook, A.F.B.; Wilson, D.J. (New Zealand Plant Protection, 2012)
A study was carried out to investigate the impact of dung pats on seeding by yellow bristle grass (Setaria pumila) Fresh cow dung was placed on dairy pasture as uniform pats in summer at two sites in Waikato New Zealand and changes in pasture attributes and earthworm abundance monitored over three grazing rotations A zone of repugnance where dairy cows avoided grazing formed out to 40 cm from the centre of the pat It was still evident at 60 days The site with highest yellow bristle grass incidence had taller and bigger yellow bristle grass seed heads in the zone resulting in over twice as much seed as control pasture Earthworm abundance was markedly higher under dung than control pasture the main species being Aporrectodea caliginosa Onfarm management strategies that may accelerate the return of the zone of repugnance to full utilization by stock and minimise weed exploitation are discussed